TRANSIENT RESPONSE ANALYSIS OF MACHINING CENTER UNDER IMPACT OF HIGH ACCELERATION - MI Jie; ZHEN Zhen; ZHU YingPing (Jixie qiangdu)
The manufacturing processing of blade,which has complicated structure and irregular surface shape,become increasingly high-speed.Thus,high acceleration is required to ensure the rapid movement of each axis.At the same time,the machining accuracy should be confirmed under the acceleration impact.The finite element model of a domestic blade machining center is established to take the transient response analysis by using ANSYS Workbench.Moreover,a new method of composite unit is presented to bolted joints and guide joints.And,the load solutions are given to linear and rotational acceleration impact.The transient responses of machining center under different accelerations are obtained,and the vibration attenuation time is analyzed to meet the machining accuracy.Thus,the impact of machine vibration on machining accuracy is minimized under high acceleration.The results provides theoretical basis for rational allocation of acceleration,optimization of the blade processing and improvement of dynamic characteristics of machining center.